2020
DOI: 10.1007/s40257-020-00527-x
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab Provides Favorable Safety and Sustained Efficacy for up to 3 Years in an Open-Label Study of Adults with Moderate-to-Severe Atopic Dermatitis

Abstract: Background Management of moderate-to-severe atopic dermatitis (AD) commonly requires long-term treatment. Objective The aim of this study was to report the safety and efficacy of dupilumab treatment for up to 3 years in adults with moderate-to-severe AD. Methods This ongoing, multicenter, open-label extension study (LIBERTY AD OLE; NCT01949311) assessed dupilumab treatment in adults previously enrolled in dupilumab trials. Patients received d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
148
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(175 citation statements)
references
References 25 publications
(77 reference statements)
18
148
2
7
Order By: Relevance
“…20,24 For comparison with exposure-adjusted incidence of skin infections in the OLE study reported here (17-25 patients per 100 PYs), a 1-year open-label study in adolescents observed skin infections in 18-34 patients per 100 PYs 14 and a 3-year open-label study in adults found the incidence to be five patients per 100 PYs. 25 The rates of conjunctivitis in the phase IIa study were small, an observation also made in a similar analysis of adolescents, 14 which could be explained in part by the short study duration and low number of dupilumab doses. Furthermore, the studies reported here were conducted before investigators developed a heightened awareness of conjunctivitis as an AE associated with dupilumab, which may lead to higher reporting in more recent studies.…”
Section: Discussionmentioning
confidence: 77%
“…20,24 For comparison with exposure-adjusted incidence of skin infections in the OLE study reported here (17-25 patients per 100 PYs), a 1-year open-label study in adolescents observed skin infections in 18-34 patients per 100 PYs 14 and a 3-year open-label study in adults found the incidence to be five patients per 100 PYs. 25 The rates of conjunctivitis in the phase IIa study were small, an observation also made in a similar analysis of adolescents, 14 which could be explained in part by the short study duration and low number of dupilumab doses. Furthermore, the studies reported here were conducted before investigators developed a heightened awareness of conjunctivitis as an AE associated with dupilumab, which may lead to higher reporting in more recent studies.…”
Section: Discussionmentioning
confidence: 77%
“…Long-term safety of up to 3 years of use of dupilumab has been established for adults [37,38]. In the group of children aged 12-17 years, safety data covers up to 52 weeks of treatment with dupilumab [39].…”
Section: Safety Of Long-term Dupilumab Therapy In Children From 6 Yeamentioning
confidence: 99%
“…Bezpieczeństwo długoterminowej terapii dupilumabem u dzieci od 6. roku życia, młodzieży i dorosłych Długoterminowe bezpieczeństwo do 3 lat stosowania dupilumabu zostało określone dla dorosłych [37,38]. U dzieci w wieku 12-17 lat dane dotyczące bezpieczeństwa obejmują czas do 52 tygodni leczenia dupilumabem [39].…”
Section: Dermatitisunclassified
“…[47]. В открытом продленном исследовании LIBERTY AD OLE (open-label extension) дупилумаб продемонстрировал благоприятный профиль безопасности и устойчивой эффективности на протяжении 3 лет наблюдений [48].…”
Section: доказательная база препарата дупилумаб у пациентов с ба хпрunclassified